Cultural destination's attributes and tourists` satisfaction: differences between first time and repeat visits - Vareiro, Laurentina (2018)
Considering the importance of tourists’ satisfaction in regards to their intentions of revisiting the destination and providing word-of-mouth referrals, this study attempts to investigate the differences between first time and repeated visitors in terms of the perceived attributes of cultural/heritage destinations, tourists’ satisfaction and intention to return and to recommend a destination. The current case study is the city of Guimarães, in Portugal. The research methodology consists of a quantitative approach based on a self-administered survey applied to tourists who visited Guimarães during 2015. Looking at the empirical results, it was possible to conclude that first time and recurrent visitors showed no noticeable difference in the way the perceived attributes of the destination were ranked. In terms of satisfaction, both first time and repeated visitors showed a high level of overall satisfaction with their visit. However, this aspect seems to be insufficient to guarantee their willingness to return. Based on the results, several recommendations may be made to increase tourists’ satisfaction vis-à-vis Guimarães, not forgetting tourists’ needs, attributes valorisation and cultural/heritage sustainability.